Physiological performance of seed and seedling of tomato under different temperatures - Gehling, Vânia Marques; Mendonça, André Oliveira; Anjos, Flávio Cunha; Allgayer, Grégor D’Ávila; Villela, Francisco Amaral; Aumonde, Tiago Zanatta (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">The objective of this study was to evaluate the physiological performance of seeds and seedlings of tomato under the influence of different temperatures. The experiment was conducted in the Didactic Laboratory of Seed Analysis – ERS, UFPel. Gaúcho® tomato seeds were used. Treatments consisted of the constant temperatures 18, 20, 22, 24 and 26 ºC. To determine the physiological performance of the seeds and seedlings were employed germination assessments, first count, germination speed index, accelerated aging, cold test, shoot and primary root length, dry matter of roots and shoots, seedling emergence at 14 and 21 days after sowing, and emergence speed index. The results showed that tomato seed germination is not affected by the temperatures 18 to 26 ºC. The first count, germination speed index and the accelerated aging values increased linearly with increasing temperature. However, the cold test and emergency, both at 14 and 21 days after sowing, were positively influenced to the approximate temperature of 22 ºC. Thus, expression of Gaúcho® tomato seed vigor is adversely affected by temperature reduction, mainly at temperatures of 18 to 20 ºC.